2010
DOI: 10.1038/jhg.2010.105
|View full text |Cite
|
Sign up to set email alerts
|

GATA transcription factors in congenital heart defects: A Commentary on a novel GATA6 mutation in patients with tetralogy of Fallot or atrial septal defect

Abstract: C ongenital heart defects (CHDs) occur in nearly 1% of all live births and are the major cause of infant mortality and morbidity. In addition, about 3 per every 1000 live births will require some intervention during the first year of life. 1 Despite its clinical importance, the underlying genetic etiology of most CHD remains unknown. Previous studies succeeded in revealing genetic causes of some syndromic or familial CHD, however, there are limited numbers of such cases, and it is still difficult to approach t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…GATA6 , a zinc finger transcription factor plays an important role in the regulation of cellular differentiation and organogenesis. Heterozygous point missense mutations in this gene are associated with several congenital defects including TOF, VSDs and ASDs [Kodo and Yamagishi, ; Lin et al, ; Maitra et al, ; OMIM 601656]. Homozygous mutations of RBBP8 have been associated with Jawad syndrome and Seckel syndrome 2 (OMIM 604124).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…GATA6 , a zinc finger transcription factor plays an important role in the regulation of cellular differentiation and organogenesis. Heterozygous point missense mutations in this gene are associated with several congenital defects including TOF, VSDs and ASDs [Kodo and Yamagishi, ; Lin et al, ; Maitra et al, ; OMIM 601656]. Homozygous mutations of RBBP8 have been associated with Jawad syndrome and Seckel syndrome 2 (OMIM 604124).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, heterozygous mutations in GATA6 have been recently shown to cause several congenital heart defects including TOF, ASDs, and VSDs in humans [Kodo and Yamagishi, ; Lin et al, ; Maitra et al, ; Padang et al, ]. GATA6 belongs to a family of transcription factors that bind to a GATA consensus motif (A/TGATAA/G).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34, 35 The Gly115Trp (G115W) mutation occurs near one of the transactivation domains of GATA4, a region in which prior mutations have been identified in patients with ASD. 36 In addition, in vitro transactivation studies demonstrate similar loss of function deficits as those identified with other disease-causing mutations. 18, 20 This mutation highlights the ability of our WES methodology to identify likely pathogenic mutations in familial CHD cases when there is limited availability of affected family members for analysis.…”
Section: Discussionmentioning
confidence: 67%